Randomised controlled trial of azathioprine withdrawal in ulcerative colitis. - Hawthorne, A. B. (1992)
OBJECTIVE--To determine whether azathioprine can prevent relapse in ulcerative colitis. DESIGN--One year placebo controlled double blind trial of withdrawal or continuation of azathioprine. SETTING--Outpatient clinics of five hospitals. SUBJECTS--79 patients with ulcerative colitis who had been taking azathioprine for six months or more. Patients in full remission for two months or more (67), and patients with chronic low grade or corticosteroid dependent disease (12) were randomised separately. 33 patients in remission received azathioprine and 34 placebo; five patients with chronic stable disease received azathioprine and seven placebo. MAIN OUTCOME MEASURE--Rate of relapse. Relapse was defined as worsening of symptoms or sigmoidoscopic appearance. RESULTS--For the remission group the one year rate of relapse was 36% (12/33) for patients continuing azathioprine and 59% (20/34) for those taking placebo (hazard rate ratio 0.5, 95% confidence interval 0.25 to 1.0). For the subgroup of 54 patients in long term remission (greater than six months before entry to trial) benefit was still evident, with a 31% (8/26) rate of relapse with azathioprine and 61% (17/28) with placebo (p less than 0.01). For the small group of patients with chronic stable colitis (six were corticosteroid dependent and six had low grade symptoms) no benefit was found from continued azathioprine therapy. Adverse events were minimal. CONCLUSIONS--Azathioprine maintenance treatment in ulcerative colitis is beneficial for at least two years if patients have achieved remission while taking the drug. Demonstration of the relapse preventing properties of azathioprine has implications for a large number of patients with troublesome ulcerative colitis, who may benefit from treatment with azathioprine.